PENINGKATAN KESADARAN SOSIAL SISWA MELALUI INTEGRASI PEMBELAJARAN IPS DALAM MENGATASI MASALAH SOSIAL - Rifdah Septianingsih; Dessy Safitri; Sujarwo, Sujarwo (Triwikrama: Jurnal Ilmu Sosial, 2024)
This research is a literature review that discusses social studies learning to build junior high school students' social awareness in overcoming social problems, with a focus on the concept of four social studies families. History helps students understand the origins of social problems, geography helps them see the geographic impact of those problems, sociology introduces the social concepts involved, and economics helps students understand the economic implications of those problems. This integration helps students develop a more comprehensive and in-depth understanding of social issues. Social awareness, which is an important aspect of this approach, refers to students' ability to identify social problems, feel empathy for affected individuals, and contribute to efforts to overcome those problems. With a focus on social awareness, social studies seeks to form students who are not only academically intelligent, but also have the ability to participate in society in a positive way. The results of this literature review underline that the integration of social studies learning with social awareness can provide significant benefits in overcoming social problems. Students who engage in this kind of learning have a better chance of becoming socially conscious members of society and playing an active role in solving social problems.